Electronic Registration in Complementary/Homeopathic Medical Practice with Identification of ‘Best Homeopathic Cases’: A Pilot Study - Klein-Laansma, Christien T.; Rutten, Alexander L. B.; Fruijtier, Paul C.; Wijtenburg, Huib H. M. (Homeopathy, 2019)
Background Practice-based registration could identify ‘general’ and ‘homeopathic’ prognostic factors for therapeutic success in patients who seek complementary and alternative medicine (CAM)/homeopathic treatment. Identification of ‘best homeopathic cases’ within a database could inform clinical research and improve homeopathic practice.Objective To investigate the feasibility of registration in daily CAM/homeopathic practice, evaluate patient-reported outcome measures and tools for identifying ‘best homeopathic cases’ and to make recommendations for an electronic database.Methods In 2015 and 2016, 25 homeopathic doctors registered details of a maximum of 20 patients each, with 6 months of follow-up (extended follow-up for ‘best homeopathic cases’), in Excel or in the Homeopathic Administration and Registration Program (HARP) database. Informed consent was obtained from each patient. Patient-perceived change of main complaint was measured by a 7-point Likert scale. Best homeopathic cases were defined by treatment with one homeopathic medicine, ≥ 2 months of follow-up, result score +2 to +4 on a 9-point Likert scale by the doctor, and by changes that could be attributed to the homeopathic medicine. Association between scores for change of main complaint and scores for ‘best homeopathic case’ was analysed by the Kruskal gamma test.Results Three-hundred and ninety-nine patients were included. In 49.1%, the main complaint was present for ≥ 2 years. The most common diagnosis was ‘fatigue’ (N = 56; 14%). Major improvement in the main complaint (score +3) was reported by 22 to 26% at consecutive follow-up visits. One-hundred and ninety-six patients were treated with a single homeopathic medicine, among whom 66 ‘best homeopathic cases’ were identified. The correlation between patient-reported changes of main complaint and assessment by the doctor was significant (gamma = 0.832; p < 0.001).Conclusions Registration of (co-)diagnoses, chronicity, treatments and outcomes in homeopathic practice with identification of ‘best homeopathic cases’ is feasible, using the tools provided. A user-friendly electronic database for efficient recording is recommended.
Keywords: complementary medicine; homeopathy; ‘best homeopathic cases’; data collection; prognostic factors